2020
DOI: 10.7759/cureus.9905
|View full text |Cite
|
Sign up to set email alerts
|

Managements for Obstructive Sleep Apnea in Adults: Review

Abstract: Obstructive sleep apnea (OSA) is characterized by recurrent obstruction of the pharyngeal airway during sleep, with resultant hypoxia and sleep fragmentation. It is more common in middle-aged obese men and prevalence is higher in most obese people. However, prevalence is high in African-Americans. OSA is associated with major comorbidities including excessive daytime sleepiness and increased risk of cardiovascular diseases. First and foremost, OSA management starts from educating patients about short-term cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This is especially relevant in our study because OSA specifically has been found to be more prevalent in the Black population. 57 , 58 This suggests that race may play a role in the prevalence of OSA. Future directions for research should focus on including a more representative study population so that racial subgrouping can be better represented.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially relevant in our study because OSA specifically has been found to be more prevalent in the Black population. 57 , 58 This suggests that race may play a role in the prevalence of OSA. Future directions for research should focus on including a more representative study population so that racial subgrouping can be better represented.…”
Section: Discussionmentioning
confidence: 99%
“…Other treatments are less common. For example, oral appliances are proven to be less effective than CPAP, especially in severe OSA [ 26 ]. Since traditional efficacy monitoring method PSG is expensive and time-consuming, the establishment of predictive biomarkers for OSA therapy response has become a priority.…”
Section: Discussionmentioning
confidence: 99%
“…The International Classification of Sleep Disorders (Third Edition) states that sleep-related respiratory disorders include obstructive sleep apnea syndrome (OSAs), central sleep apnea syndrome (CSAs), sleep-related hypopnea disorder, and sleep-related hypoxemia disorder. [ 1 ] The most common type is OSAs, characterized by partial or complete collapse of the upper airway during sleep, [ 2 ] causing snoring, morning headaches, daytime sleepiness, memory loss, and a series of symptoms. The incidence rate of CSAs is significantly lower than that of OSAs, and it is not related to anatomic obstruction but to insufficient respiratory drive leading to ventilatory disorders.…”
Section: Introductionmentioning
confidence: 99%